О движении вращающегося шара переменной массы - Ольшанский, В. П.; Ольшанский, Станислав Васильевич (НТУ "ХПИ", 2009)
Розв’язано рівняння падіння однорідного шару змінного радіуса з вертикальною віссю обертання без урахування опору зовнішнього середовища. За лінійного закону зміни радіуса в часі перші інтеграли рівняння руху виражені в елементарних функціях, а другі, для початкового етапу руху, зведені до інтегралів Френеля.

The equations of fall of a homogeneous sphere with variable radius and a vertical axis of rotation without the account of resistance of external environment are solved. At the linear law of change of radius in time the first integrals of the equation of motion are expressed in elementary functions, and second, for the initial stage of movement, are shown to Fresnel’s integrals.
Keywords: сила Магнуса; сферическое тело; возрастающий радиус; интегралы Френеля